A comprehensive analysis of twin births: clinical characteristics, morbidity trends, and risk determinants - Parvin, Nazma; Naher, Begum Sharifun; Shamim, Kazi Farhana Binta; Chowdhury, Golam Riad (International Journal of Contemporary Pediatrics, 2024)
Background: Twin births are often associated with increased risks and complications compared to singleton births. This study aims to analyze the clinical profile, morbidity pattern, and risk factors associated with twin births, focusing on maternal characteristics, neonatal outcomes, and the prevalence of conditions such as low birth weight (LBW) and preterm births. Methods: This hospital-based observational study was conducted at a tertiary care center, involving 25 mothers who had given birth to twins and their 50 neonates. The study assessed maternal age, antenatal care, parity, medical history, and neonatal outcomes including birth weight, gestational age, respiratory and cardiac parameters, and overall health status. Data were collected through medical records and direct observations in the neonatal intensive care unit. Results: The majority of mothers (64%) were aged between 21-30 years, with a mean age of 24.8 years. A significant proportion (92%) had regular antenatal visits, and 96% were multiparous. The majority of neonates (68%) were aged ≤12 hours at assessment, with a near-equal distribution between very low birth weight (VLBW) and LBW. Preterm births were common, affecting 84% of the neonates. Respiratory challenges were evident, with 62% of neonates having SpO2 levels below 94%. The mortality rate among the neonates was 32%. Conclusions: The study highlights the high-risk nature of twin pregnancies, characterized by a significant prevalence of LBW, VLBW, and preterm births. The findings emphasize the need for enhanced prenatal care and specialized neonatal interventions. The high mortality rate among neonates indicates the critical need for targeted strategies to improve neonatal outcomes in twin pregnancies. These insights are crucial for informing clinical practices and developing comprehensive care protocols for managing twin pregnancies and their associated risks.